Relationship between Employee Training Programs and Organizational Performance in Technology Companies in DRC - Lubondo, Kiripi (European Journal of Human Resource, 2024)
Purpose: The aim of the study was to assess the relationship between employee training programs and organizational performance in technology companies in DRC. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study examining the relationship between employee training programs and organizational performance in technology companies have consistently shown a positive correlation. Study indicates that investing in training programs leads to improved employee skills, knowledge, and productivity, which in turn positively impact organizational performance metrics such as profitability, innovation, and market competitiveness. Effective training programs not only enhance individual employee performance but also contribute to a culture of continuous learning and adaptation within the organization, crucial in the rapidly evolving landscape of technology. Additionally, companies that prioritize training demonstrate higher employee satisfaction, lower turnover rates, and greater employee engagement, further bolstering overall organizational effectiveness and success in the dynamic tech industry. Implications to Theory, Practice and Policy: Human capital theory, social learning theory and resource-based view of the firm may be used to anchor future studies on assessing relationship between employee training programs and organizational performance in technology companies in DRC. Based on empirical findings, technology companies can design and implement evidence-based training interventions that are tailored to their specific organizational contexts and objectives. Policymakers should recognize the importance of employee training and development in driving economic growth, innovation, and competitiveness in the technology sector.